2023
DOI: 10.1155/2023/3800810
|View full text |Cite
|
Sign up to set email alerts
|

Population- and Gender-Based Investigation for Prevalence of Helicobacter pylori in Dhamar, Yemen

Abstract: Among 35 species of genus Helicobacter, H. pylori is the most common causative agent of human gastritis, peptic ulcer, and gastric cancer. The infection can spread through direct human-to-human contact, fecal–oral route, and contaminated water. The study was designed to investigate the rate of prevalence of H. pylori in the population of Dhamar, Yemen. In this one-year study, 460 including 250 male and 210 female stool specimens were collected between January to December 2020 in Dhamar Governorate, Yemen. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…In addition, from this study it was found that women are more at risk of H. Pylori infection than men, although this is not statistically significant. In a study conducted in Yemen, there was no gender difference between males and females in patients infected with H. Pylori (16). Gender is also not dominant towards men or women, but the frequency of occurrence is higher in men (25.8%) than women (18.9%) (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, from this study it was found that women are more at risk of H. Pylori infection than men, although this is not statistically significant. In a study conducted in Yemen, there was no gender difference between males and females in patients infected with H. Pylori (16). Gender is also not dominant towards men or women, but the frequency of occurrence is higher in men (25.8%) than women (18.9%) (17).…”
Section: Discussionmentioning
confidence: 99%
“…The host immune response to H. Pylori is very complex and can change depending on age, where during childhood the predominant pattern of inflammation (Treg), with higher concentrations of TGF-β1 and IL-10, makes the gastric mucosa of children more vulnerable. Against H. Pylori colonization (16). In adults the dominant Th1 response, with higher levels of IFN-γ and IL-12p70 in the gastric mucosa thereby inducing excessive inflammatory activity and causing a greater risk of gastric damage (18).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Yemen by Almashhadany and Mayass (2018) showed that women are more exposed to H. pylori infection with a prevalence of 85.71%, compared to 76.71% in men. According to Elmanama et al (2008), there is no significant difference in the overall prevalence of H. pylori infection between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…The most active measure is to prevent the acquisition of the disease by avoiding risk factors for T. gondii infection, particularly practice good hygiene. However, we can summarize the procedures (10.1 to 10.10) can significantly reduce the risk of toxoplasmosis [70][71][72][73][74][75].…”
Section: Prevention and Controlmentioning
confidence: 99%